Implementasi Program Puspaga (Pusat Pembelajaran Keluarga) Sebagai Upaya Preventif terhadap Permasalahan Perempuan dan Anak di Kota Surabaya - Achmad Fais Mauludin; Muhammad Agus Muljanto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The purpose of this research is to find out how the PUSPAGA (Family Learning Center) Program is implemented as a preventive measure for women and children's problems in the city of Surabaya. This research is based on the problem of still finding many cases related to violence against women and children in the city of Surabaya as well as the lack of awareness and enthusiasm of the community who are willing to use PUSPAGA services. The theoretical basis used in this research uses the policy implementation theory according to Van Meter Van Horn which created 6 dimensions in viewing the success of a policy implementation program. This research uses qualitative techniques in the form of a case study. Some data collection is through observation, indirect interviews, documentation and archival records. The results of this research show that the implementation of the PUSPAGA (Family Learning Center) Program as an effort to prevent women's and children's problems in the city of Surabaya is running quite well. There are many various problem cases handled by Puspaga Kota Surabaya. Obstacles in the PUSPAGA Program in Surabaya City are the lack of community participation and openness in using PUSPAGA services, several Information and Education Communication (KIE) media which are intensively carried out by PUSPAGA Surabaya City, for example in the form of posters, posting video reels, brochures and banners to provide in-depth understanding. related to the function of establishing the Puspaga Program and providing information and education regarding the openness of free counseling/consultation services to all the people of Surabaya City.